ChemInform Abstract: Hydrothermal Synthesis of Single Crystal CoAs2O4 and NiAs2O4 Compounds and Their Magnetic Properties. Issue 21 (May 2015) - Dordevic, Tamara; Wittwer, Astrid; Jaglicic, Zvonko; Djerdj, Igor
Abstract Single crystals of CoAs2O4 (I) are grown under hydrothermal conditions using an aqueous 1:1:1 molar mixture of KCl, Co(OH)2, and As2O3 at pH 6 (autoclave, 200 °C, 199 h; cooling to 25 °C within 98 h).